1988
DOI: 10.1159/000181055
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine and Immunological Findings in Cryptorchid Infants

Abstract: In cryptorchid infants, significantly decreased mean levels of plasma testosterone and luteinizing hormone (LH) were found between the ages of 30 and 120 days. The levels of testosterone and LH were significantly correlated. No significant difference was found between infants with bilateral or unilateral cryptorchidism. After 120 days there was no longer any significant difference between cryptorchid infants and controls. No significant change in plasma follicle-stimulating hormone (FSH) was found. These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
2

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 17 publications
0
26
0
2
Order By: Relevance
“…Raivio et al 9 reported that androgen bioactivity at 3 months of age correlated with serum testosterone concentration and cryptorchid boys had reduced androgen bioactivity. In some studies, decreased serum testoterone levels together with reduced luteinizing hormone (LH) levels have been found 10,11 . The androgen effect is necessary but not sufficient alone for normal testicular descent.…”
Section: Hormonesmentioning
confidence: 99%
“…Raivio et al 9 reported that androgen bioactivity at 3 months of age correlated with serum testosterone concentration and cryptorchid boys had reduced androgen bioactivity. In some studies, decreased serum testoterone levels together with reduced luteinizing hormone (LH) levels have been found 10,11 . The androgen effect is necessary but not sufficient alone for normal testicular descent.…”
Section: Hormonesmentioning
confidence: 99%
“…Decreased serum testosterone and LH levels have been reported in some studies [32,33] but endocrine abnormalities are not always detected. In our study, a clear pattern of hormonal changes was seen in Finnish cryptorchid boys [31].…”
mentioning
confidence: 99%
“…Serum levels of AMH are normal in neonates with cryptorchidism but are lower than normal at 4±12 months of age [1]. Also steroidogenesis, which is normal at birth in babies with cryptorchidism [3,8], can become deranged within a few months after birth [3]. In both our patients, no evidence of testicular endocrine dysfunction was present at the time of diagnosis, as con®rmed by the hCG stimulation test and, clinically more important, by the spontaneous onset of puberty in our older patient.…”
Section: Discussionmentioning
confidence: 99%